2017
DOI: 10.1016/j.bbmt.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

The Case for High Resolution Extended 6-Loci HLA Typing for Identifying Related Donors in the Indian Subcontinent

Abstract: Three-loci low-resolution (LR) or intermediate-resolution HLA typing is generally considered adequate in the related blood and marrow transplantation (BMT) context. However, a single high-resolution (HR) mismatch may have a similar adverse impact on BMT outcome as an LR one. We sought to determine the frequency of mismatches that may go undetected when standard typing (LR or 3-loci HR) is used compared with 6-loci HR typing for related donor compatibility testing, and to assess its impact on relevant BMT outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017). With a 3-field resolution, our typing process can distinguish between HLA-A * 24:02:01, HLA-A * 24:02:13, and HLA-A * 24:02:40 and between HLA-C * 07:01:01 and HLA-C * 07:01:02, which are considered high-resolution mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017). With a 3-field resolution, our typing process can distinguish between HLA-A * 24:02:01, HLA-A * 24:02:13, and HLA-A * 24:02:40 and between HLA-C * 07:01:01 and HLA-C * 07:01:02, which are considered high-resolution mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…All of our mother donors (2 in regimen A and 8 in regimen B) were 12/12 HLA identical by high-resolution typing. It is likely that they were fully genoidentical due to a high degree of consanguinity, resulting in shared haplotypes within families among the South Asian population [49].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of candidates suitable for transplantation led to 391 patients getting human leukocyte antigen-typed and prepared for bone marrow transplantation from these centers. In all, 43 were transplanted with overall survival of 93% and disease-free survival of 77% at a mean cost of US $13,000 per transplant, including pretransplant preparation and late complications [45,46]. For these patients, online software specific for bone marrow transplantation was used [47].…”
Section: Resultsmentioning
confidence: 99%